Answer:
-(9 x^2 + 15 x - 2)
Explanation:
Simplify the following:
-(8 x^2 + 8 x + 8) - x^2 - 7 x + 10
Factor 8 out of 8 x^2 + 8 x + 8:
-x^2 - 7 x + 10 - 8 (x^2 + x + 1)
-8 (x^2 + x + 1) = -8 x^2 - 8 x - 8:
-8 x^2 - 8 x - 8 - x^2 - 7 x + 10
Grouping like terms, -x^2 - 8 x^2 - 7 x - 8 x - 8 + 10 = (-x^2 - 8 x^2) + (-7 x - 8 x) + (10 - 8):
(-x^2 - 8 x^2) + (-7 x - 8 x) + (10 - 8)
-x^2 - 8 x^2 = -9 x^2:
-9 x^2 + (-7 x - 8 x) + (10 - 8)
-7 x - 8 x = -15 x:
-9 x^2 + -15 x + (10 - 8)
10 - 8 = 2:
-9 x^2 - 15 x + 2
Factor -1 out of -9 x^2 - 15 x + 2:
Answer: -(9 x^2 + 15 x - 2)